Padrões e processos em diversidade funcional e o uso de atributos para predição - Gonzaga, Alice Francener Nogueira (2019)
Community ecology studies patterns of diversity and the processes underlying those patterns. In general, many of these studies consider only taxonomic diversity. However, functional diversity, a component that considers the ecological role of species, can also be used to understand the processes that structure diversity patterns. This approach allows us to understand the relationships between species and the environment. In addition, functional diversity can also provide relevant information for biodiversity conservation planning and can help make predictions in community ecology. Thus, this study had the following main objectives: (i) to analyze the theoretical structure, limitations and applications of models that use the relationship of environment and species tratis to make predictions; (ii) test whether the environment determines the functional similarity of biological communities; (iii) analyze how the order of bird species discoveries and the possible extinction influence the rate of discovery and loss of functional diversity. As a result for (i) we list some limitations and problems in models that use the relationship between environment and species traits to make predictions in communities, as well as examples of applications for these models. Considering objective (ii), we observed that the turnover of functional diversity can be explained by both environmental variables and biogeography. As a result of objective (iii) we observed that functional diversity was discovered faster than expected by chance and that the new species described contribute little to the known functional diversity. Additionally, if threatened and data deficient species were more likely to become extinct, functional diversity will be lost more slowly than expected by chance. Thus, we conclude that the use of measures that capture ecological aspects of species allows us to understand important patterns that could not be easily observed using taxonomic diversity alone.